A targeted and synergetic nano-delivery system against Pseudomonas aeruginosa infection for promoting wound healing - Chang Ni; Xisheng Li; Haiye Jiang; Shumin Gui; Heng Yin; Xinmin Nie (Materials Today Bio)
Purpose: Pseudomonas aeruginosa infection is the most common pathogen in burn wound infections, causing delayed wound healing and progression to chronic wounds. Therefore, there is an urgent need to develop antimicrobial agents that can promote wound healing for effectively treating infected wounds. Patients and methods: Using magnetic stirring and ultrasound to synthesize Apt-pM@UCNPmSiO2-Cur-CAZ. The nanosystems were characterized using transmission electron microscopy (TEM), dynamic light scattering (DLS), and ultraviolet–visible spectrophotometry (UV–Vis). Flow cytometry, bacterial LIVE/DEAD staining and scanning electron microscopy were performed to assess the in vitro antibacterial and anti-biofilm effects of the nanosystems. The wound healing potential and in vivo toxicity of the nanosystems were evaluated in a mouse skin wound model. Results: The Apt-pM@UCNPmSiO2-Cur-CAZ synthesized exhibited uniform circular shape with a Zeta potential of −0.8 mV. In vitro, Apt-pM@UCNPmSiO2-Cur-CAZ demonstrated superior antibacterial effects compared to standalone antibiotics. Bacteria treated with Apt-pM@UCNPmSiO2-Cur-CAZ showed varying degrees of deformation and shrinkage, resulting in severe damage to the bacterial cells. Additionally, Apt-pM@UCNPmSiO2-Cur-CAZ can inhibit and eradicate bacterial biofilms, while also targeting bacteria for enhanced antibacterial efficacy. Interestingly, the NIR light could enhance the antibacterial and anti-biofilm effects of Apt-pM@UCNPmSiO2-Cur-CAZ due to the photodynamic action. In a mouse skin wound infection model, the nanosystem effectively eliminated wound bacteria, promoting the healing of Pseudomonas aeruginosa-infected wounds without significant toxic effects. Conclusion: Apt-pM@UCNPmSiO2-Cur-CAZ is a novel targeted nano-delivery system with promising potential in combating Pseudomonas aeruginosa infections, and it may serve as a new therapeutic approach for treating skin wound infections.